PROSES PENYELESAIAN SENGKETA PEMBATALAN PERKAWINAN KARENA ADANYA PENIPUAN MENGENAI DIRI ISTRI(Studi Kasus di Pengadilan Agama Surakarta) - EVRIANI, AYU; , Nuswardhani, S.H., S.U; , Mutimatun Ni'ami S.H (2015)
This thesis examines about the process of completion cancellation dispute of marriage because deception concerning self-wife. The method is the author using normative juridical method that aims to describe the process of completion cancellation dispute of marriage because deception concerning self-wife. Primary data of this study is the decision Islamic Court of Surakarta No. 0033/Pdt.G/ 2015/PA.Ska. Secondary data of this study is the material that gives a description of the primary legal materials, such as research results, the opinion of legal experts, and scientific journals that have anything to do with the case of petition for cancellation of the marriage because deception concerning self-wife. Research results the decision Islamic Court of Surakarta No.0033/Pdt.G/2015/PA.Ska is the judge in determining evidentiary consider the evidences is submitted by the Applicant at the trial. Whereas the judge in determining the verdict using verdict verstek for to grant the petition. And as a the legal consequences due to the cancellation of marriage is a marriage between the Applicant and the Respondent considered has never been happened, and the decision the cancellation of the marriage apply retroactive to of children birth outside of marriage. Keywords: Cancellation of Marriage, Deception Concerning Self-wife